Design for three-dimensional stabilization control of underactuated autonomous underwater vehicles. (15th February 2018) - Li, Yiming; Li, Ye; Wu, Qi
Abstract: In order to realize three-dimensional stable control of underactuated autonomous underwater vehicles (AUVs), this study analyses nonlinear hydrodynamic characteristics of AUVs based on the mathematical Taylor series. The nonholonomic control system properties of AUVs are investigated using nonholonomic system theory under three-dimensional control input. The constraint of underactuated AUVs is proved not to be integrated by the local integrability theorem, and the controllability of underactuated AUVs is verified through small-time local controllability (STLC). In order to simplify the trigonometric terms in underactuated AUV motion functions, quaternion theory is applied to transform the function to develop a continuous time-varying controller. Results of a simulation experiment show that this control law is effective in achieving three-dimensional stabilization from arbitrary initial positions. Highlights: Nonlinear hydrodynamic characteristics of AUVs are studied based on the Taylor series. A continuous, time-varying controller is proposed based on the AUV spatial motion. Simulation results show that the developed controller is effective.